1998
DOI: 10.1086/301974
|View full text |Cite
|
Sign up to set email alerts
|

Fine Mapping of the Diabetes-Susceptibility Locus, on Chromosome 11q13

Abstract: Genomewide linkage studies of type 1 diabetes (or insulin-dependent diabetes mellitus [IDDM]) indicate that several unlinked susceptibility loci can explain the clustering of the disease in families. One such locus has been mapped to chromosome 11q13 (IDDM4). In the present report we have analyzed 707 affected sib pairs, obtaining a peak multipoint maximum LOD score (MLS) of 2.7 (lambda(s)=1.09) with linkage (MLS>=0.7) extending over a 15-cM region. The problem is, therefore, to fine map the locus to permit st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2000
2000
2003
2003

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 33 publications
1
41
0
Order By: Relevance
“…In a two-stage approach 2042 families were genotyped for markers from this region, and a specific haplotype comprising alleles of the two polymorphic markers, D11S1917 and H0570polyA, showed decreased transmission (46.4%) to affected offspring and increased transmission (56.6%) to unaffected siblings. 117 Several potential candidate genes map to the region near FGF3 in humans, including ZFM1 (zinc finger protein 162), which encodes a putative nuclear protein demonstrable in the pancreas. 118 The gene encoding the Fas-associated death domain protein (FADD) has also been mapped to this region.…”
Section: Iddm2-the Insulin Gene (Ins) Regionmentioning
confidence: 99%
“…In a two-stage approach 2042 families were genotyped for markers from this region, and a specific haplotype comprising alleles of the two polymorphic markers, D11S1917 and H0570polyA, showed decreased transmission (46.4%) to affected offspring and increased transmission (56.6%) to unaffected siblings. 117 Several potential candidate genes map to the region near FGF3 in humans, including ZFM1 (zinc finger protein 162), which encodes a putative nuclear protein demonstrable in the pancreas. 118 The gene encoding the Fas-associated death domain protein (FADD) has also been mapped to this region.…”
Section: Iddm2-the Insulin Gene (Ins) Regionmentioning
confidence: 99%
“…However, this process is fraught with difficulties. For example, IDDM4 was mapped to FGF3 on chromosome 11q13 by three groups [58,61,62] and subsequent studies showed maximal linkage at D11S1337 just proximal to FGF3, with MLS 3.9 [59,63] and MLS 2.7 [64]. Thus, it is likely that this represents a true linkage.…”
Section: Is Positional Candidate Mapping Feasible?mentioning
confidence: 99%
“…Thus, it is likely that this represents a true linkage. However, MLS values of at least 1.7 extended over a wide 15 cM region [64]. It is characteristic of linkages for genes predisposing to complex disorders that true linkage peaks tend to be broader than false peaks [118], but this also makes it difficult to define a reasonable interval for intensive disequilibrium mapping.…”
Section: Is Positional Candidate Mapping Feasible?mentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] However, theoretical studies in the mid-1980s suggested that genes outside the HLA region may contribute more than half of the genetic susceptibility to this form of diabetes. 4 Since then, many putative diabetes-predisposing genes outside the HLA region have been localised, including IDDM2 in the insu-lin gene region 5 (HLA region predisposition is now collectively referred to as IDDM1), IDDM3, [6][7][8] IDDM4, 6,[9][10][11][12] IDDM5, 9,11 IDDM6, 13 IDDM7, 14,15 IDDM8, 7,11 IDDM10, 16,17 IDDM11, 18 IDDM12, [19][20][21] IDDM13, 21,22 IDDM15, 23 IDDM17, 24 IDDM18, 25 and other putative localisations currently without an IDDM designation. 17,[26][27][28][29] Thus, it is now clear that while HLA region genes contribute the major predisposition to type 1 diabetes, there are numerous other genes with smaller effects on susceptibility.…”
Section: Introductionmentioning
confidence: 99%